2021
DOI: 10.5194/acp-2021-675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced summertime ozone and SOA from biogenic volatile organic compound (BVOC) emissions due to vegetation biomass variability during 1981–2018 in China

Abstract: Abstract. Coordinated control of fine particulate matter (PM2.5) and ozone (O3) has become a new and urgent issue for China’s air pollution control. Biogenic volatile organic compounds (BVOCs) are important precursors of O3 and secondary organic aerosol (SOA) formation. China experienced a rapid increase in BVOC emissions as a result of increased vegetation biomass. We applied WRF-Chem3.8 coupling with MEGAN2.1 to conduct long-term simulations for impacts of BVOC emissions on O3 and SOA during 1981–2018, using… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…For a detailed breakdown of emissions attributable to varied land use covers, refer to Table S4. A review of the data reveals that monoethylene (TERP) and isoprene (ISOP) rank as the highest emitting species with proportions are 20.46% and 31.91% in this study, respectively, aligning with the findings of previous studies (Cao et al, 2022;Guenther et al, 2012b). Furthermore, Table 5 reveals that in September, the suburban region registered the highest UGS-BVOC emissions in Guangzhou, peaking at 367.31 Gg.…”
Section: Estimation Of Ugs-bvoc Emissions Under Different Land Use Coversupporting
confidence: 88%
“…For a detailed breakdown of emissions attributable to varied land use covers, refer to Table S4. A review of the data reveals that monoethylene (TERP) and isoprene (ISOP) rank as the highest emitting species with proportions are 20.46% and 31.91% in this study, respectively, aligning with the findings of previous studies (Cao et al, 2022;Guenther et al, 2012b). Furthermore, Table 5 reveals that in September, the suburban region registered the highest UGS-BVOC emissions in Guangzhou, peaking at 367.31 Gg.…”
Section: Estimation Of Ugs-bvoc Emissions Under Different Land Use Coversupporting
confidence: 88%
“…In contrast, the south regions of YRD demonstrate a universal pattern of NO x -limited. This could be attributed to the substantial biogenic VOCs emissions from the forest districts in Zhejiang province (Cao et al, 2021). Other YRD regions are mainly controlled by both NO x and VOCs.…”
Section: Driving Factors Of Interannual Changes In O 3 From 2014 To 2020mentioning
confidence: 99%
“…Areas of low altitude and vegetation with short root systems are more sensitive. Based on simulations from the Model of Emissions of Gases and Aerosols from Nature (MEGAN) (Guenther et al, 2006(Guenther et al, , 2012 and using MODIS LAI between 2003, Cao et al (2021 found that vegetation biomass variability in China is a major controlling factor of the interannual variation of BVOC emissions.…”
Section: Introductionmentioning
confidence: 99%